GLOBAL RESEARCH TRENDS IN SPECIAL EDUCATION: A BIBLIOMETRIC ANALYSIS - Affendi, Sofea Hanim (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This bibliometric analysis investigates global research trends in the field of special education over an 11-year period from 2015 to 2025. Special education has increasingly gained prominence due to its role in promoting inclusivity and addressing diverse learning needs, particularly through the integration of digital tools and evidence-based practices. Despite policy advances and technological innovations, disparities in implementation and access persist globally. To examine the evolution of scholarly focus in this area, 939 articles were systematically retrieved from the Scopus database using precise inclusion criteria, including language, publication type, and thematic relevance to students with special needs. The data were cleaned using OpenRefine and further analysed through VOSviewer to identify patterns in keyword co-occurrence, author co-citation, and country-level collaboration. The results revealed a consistent upward trend in publication output, peaking in 2024, with the United States leading in contributions, followed by Turkey, the United Kingdom, and Saudi Arabia. The most frequently cited works address critical themes such as disproportionality in special education placement, teacher attrition, and inclusive pedagogy. Prominent research clusters emerged around inclusive education policies, professional development, social equity, and mental health of educators. Keyword mapping indicated a shift from foundational topics to emerging concerns like e-inclusion, multilingual learners, and burnout among special education teachers. Co-citation and co-authorship analyses highlighted influential authors and collaborative networks shaping the discourse. While the findings underscore growing global interest in special education, they also point to underrepresentation from certain regions, signalling opportunities for broader engagement. This study not only provides a comprehensive overview of the intellectual landscape in special education but also informs future research directions, policy formulation, and professional development strategies to enhance educational equity worldwide.